ON THE METHOD OF DETECTING CHANGES IN TREND USING PERMUTATION TESTS - Miłek, Michał; Kończak, Grzegorz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article presents a proposal of the test for detecting changes in trend. The proposed procedure refers to the permutation test. The use of this procedure allowed the adoption of fairly general assumptions. The proposed method can be used, in particular to detect the appearance of the trend. In this case, it is possible to use this method to monitor industrial processes. The proposed method was compared with known from literature methods used to detect disturbances in monitoring processes. For comparing procedures computer simulations were used.